2019
DOI: 10.1021/acsomega.9b03149
|View full text |Cite
|
Sign up to set email alerts
|

Solar-Blind UV Photodetector Based on Atomic Layer-Deposited Cu2O and Nanomembrane β-Ga2O3 pn Oxide Heterojunction

Abstract: Herein, we present a solar-blind ultraviolet photodetector realized using atomic layer-deposited p-type cuprous oxide (Cu2O) underneath a mechanically exfoliated n-type β-gallium oxide (β-Ga2O3) nanomembrane. The atomic layer deposition process of the Cu2O film applies bis(N,N′-di-secbutylacetamidinato)dicopper(I) [Cu(5Bu-Me-amd)]2 as a novel Cu precursor and water vapor as an oxidant. The exfoliated β-Ga2O3 nanomembrane was transferred to the top of the Cu2O layer surface to realize a unique oxide pn heteroju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
18
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 32 publications
(52 reference statements)
0
18
0
1
Order By: Relevance
“…For example, Bae et al fabricated the Cu 2 O/β-Ga 2 O 3 pn heterojunction PD with a suspended structure via a complex process. 17 The device shows an undesired photoresponse under UV illumination, which could be attributed to the poor interface contact between Cu 2 O and β-Ga 2 O 3 . He et al reported β-Ga 2 O 3 /BP heterostructure PD, the device exhibits obviously photoresponse in UV/IR dual-band detection.…”
mentioning
confidence: 98%
See 2 more Smart Citations
“…For example, Bae et al fabricated the Cu 2 O/β-Ga 2 O 3 pn heterojunction PD with a suspended structure via a complex process. 17 The device shows an undesired photoresponse under UV illumination, which could be attributed to the poor interface contact between Cu 2 O and β-Ga 2 O 3 . He et al reported β-Ga 2 O 3 /BP heterostructure PD, the device exhibits obviously photoresponse in UV/IR dual-band detection.…”
mentioning
confidence: 98%
“…However, due to the unintentional oxygen vacancies-induced self-compensation and extremely flat valence band maximum of O 2 p -derived orbital, p -type doping in Ga 2 O 3 remains an unresolved challenge. , The absence of p -type Ga 2 O 3 hinders the development of Ga 2 O 3 pn homojunction devices. On the other hand, some attempts to build pn heterojunctions were carried out by combining p -type semiconductors such as NiO, Ir 2 O 3 , SiC, Si, Cu 2 O, and GaN with n -type Ga 2 O 3 . , Although considerable achievements have been done in the fabrication of pn heterojunctions, dislocations and defects are commonly observed, owing to the lattice mismatch and incompatible crystal structure, resulting in a degraded photoresponse characteristics. For example, Bae et al fabricated the Cu 2 O/β-Ga 2 O 3 pn heterojunction PD with a suspended structure via a complex process .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Among these process modules, ALD has advantages for device manufacturing because it produces conformal films with good spatial uniformity at relatively low processing temperatures. ALD is based on self-limiting surface chemical reactions, which enables precise control of film thickness and composition. , While a wide range of studies have reported ALD of Cu metal, a narrower set of papers have explored ALD of CuO x . , Thermal ALD of Cu 2 O and CuO thin films has been previously reported, where control over the phase and bulk oxidation state was achieved using ozone and water coreactants with a bis­(dimethylamino-2-propoxide)­copper­(II) [Cu­(dmap) 2 ] precursor . Control of crystallinity and morphology in copper oxide deposited by thermal ALD has also been achieved by varying the deposition temperature or the number of ALD cycles using a range of precursors. …”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, while postdeposition annealing (PDA) is known to tune the structural and electronic properties of CuO x deposited by other methods, ,, PDA has not been reported yet for PE-ALD CuO x . Many works that investigate the ALD process-structure relationships either do not study the p-type semiconducting properties ,, or do not directly control the electronic properties of the film by varying composition, phase, and morphology. ,, In particular, there have been only two studies, to date, that fabricated ALD Cu 2 O TFTs, neither of which used PE-ALD. , Therefore, more work needs to be done to (1) identify Cu precursors, PE-ALD processes, and PDA conditions that enable precise control of Cu oxidation state and CuO x phase and (2) identify the coupled relationships between film structure and the resulting electronic properties.…”
Section: Introductionmentioning
confidence: 99%